Effect of Corticosteroids on Pain Relief Following Root Canal Treatment: A Systematic Review - Iranmanesh, Foad; Parirokh, Masoud; Haghdoost, Ali Akbar; Abbott, Paul V. (Iranian Endodontic Journal, 2017)
Introduction: Post-operative pain and flare-up may occur in up to 58% of patients following root canal treatment. The aim was to conduct a systematic review and a possible meta-analysis to determine the effect of glucocorticosteroid (GCS) on pain following root canal treatment. Methods and Materials: Scopus, MEDLINE and CENTRAL databases were searched up to 30th January 2017 with broad key words. In addition, the reference lists in eligible papers and text books were hand-searched. Assessment of the eligibility of papers and data extraction were performed by two independent reviewers. Results: Of 9891 articles, 18 were recruited as eligible papers. Most of these papers showed pain reducing effect of GCS on post-endodontic pain. Because of wide heterogeneity among the recruited papers, it was not possible to perform meta-analysis. Conclusion: Based on the results of this systematic review, there is a vast heterogeneity amongst articles regarding the use of GCS and their effect on post-operative pain after endodontic treatment. Further investigations with similar methods and materials are needed before meta-analysis on the effect of GCS on post-operative pain following root canal treatment can be performed Keywords: Corticosteroid; Endodontics; Flare-Up; Meta-Analysis; Post-Operative Pain; Systematic Review